Epidemiology and Survival of Systemic Sclerosis-Systemic Lupus Erythematosus Overlap Syndrome - Alharbi, Samar; Ahmad, Zareen; Bookman, Arthur A; Touma, Zahi; Sanchez-Guerrero, Jorge; Mitsakakis, Nicholas; Johnson, Sindhu R (Journal of rheumatology, 2018)
Systemic sclerosis (SSc) may overlap with systemic lupus erythematous (SLE). Little is known about the epidemiology, clinical characteristics, and survival of SSc-SLE overlap. We evaluated the prevalence of SSc-SLE overlap and differences in SSc characteristics, and compared survival with SSc without SLE. A cohort study was conducted including subjects who fulfilled the American College of Rheumatology (ACR)/European League Against Rheumatism classification criteria for SSc and/or the ACR criteria for SLE. The primary outcome was time from diagnosis to all-cause mortality. Survival was evaluated using Kaplan-Meier and Cox proportional hazard models. We identified 1252 subjects (SSc: n = 1166, SSc-SLE: n = 86) with an SSc-SLE prevalence of 6.8%. Those with SSc-SLE were younger at diagnosis (37.9 yrs vs 47.9 yrs, p < 0.001), more frequently East Asian (5.5% vs 20%) or South Asian (5.1% vs 12%), had lupus anticoagulant (6% vs 0.3%, p < 0.001), anticardiolipin antibody (6% vs 0.9%, p < 0.001), and pulmonary arterial hypertension (PAH; 52% vs 31%, p < 0.001). Those with SSc-SLE less frequently had calcinosis (13% vs 27%, p = 0.007), telangiectasia (49% vs 75%, p < 0.001), and diffuse subtype (12% vs 35%, p < 0.001). There were no significant differences in the occurrence of renal crisis (7% vs 7%), interstitial lung disease (ILD; 41% vs 34%), and digital ulcers (38% vs 32%). Those with SSc-SLE had better median survival time (26.1 vs 22.4 yrs), but this was not statistically significant (log-rank p = 0.06). Female sex and diffuse subtype attenuated survival differences between groups (HR 1.07, 95% CI 0.67-1.67). Patients with SSc-SLE are younger at diagnosis, more frequently have PAH, and less frequently have cutaneous manifestations of SSc. They should be monitored for ILD, renal crisis, and digital ulcers.